Livro-reportagem “Paraíba no Prato, Orgulho no Peito”: a gastronomia armorial paraibana e a trajetória do chef Onildo Rocha - Barbosa, Tatiana Ramalho (2021)
This report presents the result of the elaboration of the book-report “Paraíba no Prato, Orgulho no Peito”, built from the perception of the growing interest in Gastronomic Journalism, addressed here as a potential tool for human knowledge and demonstration of people's traditions and customs of a place. It is currently observed that in various journalistic contexts, gastronomy is being treated as a cultural phenomenon, requiring increasingly elaborate reports, and establishing itself as an important specialty. Thus, this research was born from the intention of telling the trajectory of chef Onildo Rocha, to represent the identity of Paraíba state, as well as to contribute to promoting the relevance of territoriality, based on local knowledge and identity customs. The choice to prepare a profile report-book aims to record the stories and work of the chef, in addition to bringing out values related to Paraíba's food, telling the story of ingredients and typical dishes from the state. Furthermore, this work is designed to draw attention to a different style of cuisine: armorial gastronomy. To this end, the theoretical path covered the areas of gastronomy, with Freixa and Chaves (2017), Standage (2010) and Cascudo (2009 and 2011); cultural journalism, with Piza (2004), Ballerini (2015), Marques de Melo (2010) and literary journalism with Pena (2017; 2019), Lima (2009) and Martinez (2008).